The Transformation of Student Social Interaction in the Digital Era: An Analysis from a Contemporary Sociological Perspective - Moh. Syarif Putra Nurdin; Melcian Febrilia Pagalu (CV Projurnal Mitra Publikasi, 2025)
The rapid expansion of digital communication technologies has fundamentally altered social interaction patterns worldwide, with university students representing a demographic particularly immersed in these transformations. This study examines the transformation of student social interaction in the digital era from a contemporary sociological perspective, focusing specifically on the Indonesian higher education context while situating these dynamics within broader global trends. The rapid expansion of digital communication platforms has reconfigured patterns of interaction, social engagement, and the construction of social relationships among university students. This research aims to analyze how digital environments reshape forms of communication, social bonding, and identity formation within student communities in Indonesia, a context characterized by high social media penetration and a young, digitally native population. Using a qualitative approach based on literature review and conceptual analysis, this study draws upon contemporary sociological theories of network society, reflexive modernity, and digital sociality to interpret current interactional dynamics. The findings indicate that student interactions are increasingly mediated by digital platforms, resulting in shifts from face-to-face communal relations toward network-based connectivity. While digital media expand access to information and social networks, they also contribute to fragmented interactions, performative identities, and the redefinition of collective belonging. The study concludes that the transformation of social interaction in the digital era reflects broader structural changes in late modern society, where technology becomes an integral dimension of everyday social life. This research contributes to sociological discourse by contextualizing student social practices within contemporary theoretical frameworks.